A New R Program for Flow‐Log Analysis of Single Holes (FLASH‐R). Issue 6 (15th March 2020) - Barbosa, Marcos B.; Terry, Neil; Day‐Lewis, Frederick D.; Bertolo, Reginaldo; Lane, John W.
Abstract: A new version of the computer program FLASH (Flow‐Log Analysis of Single Holes) is presented for the analysis of borehole vertical flow logs to estimate fracture (or layer) transmissivities and far‐field hydraulic heads. The program is written in R, an open‐source environment. All previous features have been retained and new features incorporated including more rigorous parameter estimation, uncertainty analysis, and improved data import. The program has a dynamic user interface compatible with most operating systems. Abstract : Article impact statement : We present a new version of FLASH, written in the R language, for analysis of borehole flow logs and estimation of aquifer properties.